Evaluating reading-writing materials for office administration students - Solihat, Siti Maryam; Darmahusni; Sumarni, Sri (JEES (Journal of English Educators Society), 2021)
Office Administration students at VHS require English reading-writing materials to assist them acquiringcompetencies as stated in SKNNI. The present study aimed to evaluate the existing materials and seektheir relevance to SKNNI. The evaluation involved three English textbooks entitled Bahasa InggrisSMA/MA/SMK/MAK for Grade X, XI, and XII through checklist method. The authors used an evaluativechecklist adapted from Cunningsworth (1995) and focused on three aspects — learning objective,language content, and text type. The results show that learning objectives in all assessed textbooksmismatch with the competencies defined in SKKNI. Likewise, language content (grammar andvocabulary) covered in those textbooks is irrelevant with language knowledge needed as the basics toattain the competencies in SKKNI. Then, the textbooks provide the kind of texts which are distinct fromthose required by SKKNI that must be business documents. Although one topic in textbook for GradeXII relates to office administration (about job application), it remains insufficient. To put it simply, thefindings indicate that the three textbooks do not correspond to the national standards, so they areinappropriate for Office Administration students. Therefore, designing reading-writing materials basedon SKNNI is the future action in response to the results of this study.